2020
DOI: 10.1021/acsbiomaterials.0c00273
|View full text |Cite
|
Sign up to set email alerts
|

Combined Silk Fibroin Microneedles for Insulin Delivery

Abstract: To reduce the pain caused by subcutaneous injections, microneedle patches as the new transdermal drug delivery method are gaining increased attention. In this study, we fabricated a composite insulin-loaded microneedle patch. Silk fibroin, a natural polymer material, was used as the raw material. The tip of the microneedle had good dissolving property and was able to dissolve rapidly to promote the release of insulin. The pedestal had the property of swelling without dissolving and was carrying insulin as a dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 36 publications
0
55
0
Order By: Relevance
“…Jin H effectively controlled the β-sheet ratio to obtain a water-stable film containing Silk I crystals [ 17 ]. Zhu M et al used combined Silk I microneedles for drug delivery of insulin delivery [ 18 ]. Previous studies showed that Silk I-based materials had a metastable structure with poor stability and short storage time.…”
Section: Introductionmentioning
confidence: 99%
“…Jin H effectively controlled the β-sheet ratio to obtain a water-stable film containing Silk I crystals [ 17 ]. Zhu M et al used combined Silk I microneedles for drug delivery of insulin delivery [ 18 ]. Previous studies showed that Silk I-based materials had a metastable structure with poor stability and short storage time.…”
Section: Introductionmentioning
confidence: 99%
“…Subcutaneous injections of silk fibroin hydrogels with encapsulated insulin enables sustained release of insulin for blood glucose control in diabetic rats [ 115 ]. Similarly, silk fibroin microneedle patches offer a sustained release of insulin via transdermal delivery, removing the need for traditional injections which require high patient compliance and careful management of injection sites to protect tissue integrity [ 116 ].…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…PDMS micro-molds have been produced, and a vacuum-based process for filling the forms with polylactic acid, polyglycolic acid, and their polymers was designed for replicating Microfabricated Master Structures [ 388 ]. The mechanical testing of the resulting needles measured the force that split the needles during axial loading and showed that this failed strength increased with the material and needle foundation diameter and decreased with the needle length [ 389 ]. The failure forces were normally much greater than the forces needed to inject MN into the skin, suggesting the mechanical properties of biodegradable polymers for MN were adequate [ 389 ].…”
Section: Current Trends and Future Perspectivementioning
confidence: 99%
“…The mechanical testing of the resulting needles measured the force that split the needles during axial loading and showed that this failed strength increased with the material and needle foundation diameter and decreased with the needle length [ 389 ]. The failure forces were normally much greater than the forces needed to inject MN into the skin, suggesting the mechanical properties of biodegradable polymers for MN were adequate [ 389 ]. Finally, the ranges of polymer MNs revealed that the permeability of human skin cadaver was improved by up to three orders of magnitude to a low-molecular tracer, a calcein, and a macromolecular, bovine serum Albumin [ 354 ].…”
Section: Current Trends and Future Perspectivementioning
confidence: 99%